Some Unanticipated Positive Effects of a juvenile Awareness Program on Adult Inmate Counselors - Keller, Robert L. (International journal of offender therapy and comparative criminology, 1993)
A contemporary juvenile awareness program operated behind bars of a typical state prison by veteran inmates is shown to have very positive social and psychological effects on inmate counselors, even though the program was designed solely to focus on the problems of juvenile offenders. The primary benefit to inmate counselors is increased self-esteem, but residual benefits also include increased social status and prestige in the prison. This research also suggests that the inmate counselors become nurturing in their relationships with their youth clients, and with fellow inmates